Needle Electromyography in the Acute Phase of Stroke: Correlation with Severity and Muscle Strength: Preliminary Findings - Bitencourt, Ana Carolina Silva; Fernandes, Thiago Dias; Bazan, Rodrigo [UNESP]; Luvizutto, Gustavo José (Wolters Kluwer, 2022)
Background: After the stroke, the development of the second motor neuron degeneration can reduce muscle strength and functional capacity. Objective: The aim of this study was to describe the electro-myographic findings in the acute phase of stroke and to correlate them with the severity and muscle strength. Material and Methods: Twenty patients were studied in the first 72 hours after stroke. The severity of the lesion was assessed using the National Institutes of Health Stroke Scale (NIHSS), and muscle strength was assessed using the Medical Research Council Scale (MRC). Sensory conduction and motor conduction were studied to exclude peripheral polyneuropathy, radiculopathies, or other neuro-muscular diseases, and electro-myography (EMG) was performed with co-axial needle electrodes in the deltoid, carpal radial extensor, vastus lateralis, and anterior tibialis at rest, slight effort and maximum effort. The associations between qualitative and quantitative variables were studied using the Chi-square test and Fisher's exact test. Results: Among the patients, 40% had abnormal EMG [positive sharp waves (PSWs), fibrillation, fasciculations, and abnormal patterns in maximum effort]. Positive correlations were found between NIHSS and PSW (p = 0.005; r = 0.65) and abnormal EMG (p = 0.017; r = 0.72), and negative correlations were found between MRC and PSW (p = 0.041; r = -0.83) and abnormal EMG (p = 0.027; r = -0.81). Conclusion: It was concluded that the main EMG findings in the acute phase of stroke were the presence of the denervation process and polyphasic motor unit potentials. These changes in EMG were correlated with stroke severity and lower muscle strength.
Keywords: Denervation; electro-myography; muscle fibrillations; muscle plasticity; positive waves; severity; stroke